2013
DOI: 10.5588/ijtld.12.0123
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among people treated for tuberculosis and human immunodeficiency virus in Rio de Janeiro, Brazil [Short communication]

Abstract: SUMMARY We measured quality of life (QOL) among individuals receiving treatment for human immunodeficiency virus (HIV; n = 45), active tuberculosis (TB; n = 44) and both TB and HIV (n = 9) in Rio de Janeiro, Brazil. Active treated TB was associated with lower physical health (absolute decrease of 0.95 standard deviation in summary score), but not mental health, among people being treated for HIV. Visual analogue scale scores were similar across all three populations, and corresponded closely to standard disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
(13 reference statements)
6
15
0
Order By: Relevance
“…Economic status plays an important role in the quality of people's lives because it involves the conflict between self-support and the difficult access to employment and income, due to lack of physical conditions relevant to illness, fear of prejudice, or low education and qualification [9]. Brazilian researchers [5,8,10,12,13,14] found that better levels of quality of life of HIV patients were related to better financial conditions, as with the results of the present study. Other study [15], also showed better QoL indicators associated with increased income.…”
Section: Discussionsupporting
confidence: 72%
“…Economic status plays an important role in the quality of people's lives because it involves the conflict between self-support and the difficult access to employment and income, due to lack of physical conditions relevant to illness, fear of prejudice, or low education and qualification [9]. Brazilian researchers [5,8,10,12,13,14] found that better levels of quality of life of HIV patients were related to better financial conditions, as with the results of the present study. Other study [15], also showed better QoL indicators associated with increased income.…”
Section: Discussionsupporting
confidence: 72%
“…These data are similar to those found in other studies 18 , 29 and, once again, are related to the immune profile of HIV-positive patients 33 and to the rates of treatment nonadherence, which are higher in this population, as demonstrated in the present study. Nevertheless, Dowdy et al 34 reported similar decreases in quality of life across groups of patients with tuberculosis, with HIV, and with tuberculosis-HIV co-infection, by using a validated self-assessment instrument. It is of note that we found no differences in the rate of multidrug-resistant tuberculosis between the groups.…”
Section: Discussionmentioning
confidence: 93%
“…In a large South African study comprising of 4900 participants, significantly lower health status and QOF were observed in HIV infected TB patients than their TB alone infected counterparts (Louw et al, 2012; Peltzer et al, 2013). The physical health summary scores were found to be significantly different in TB patients with or without HIV co-infection (Dowdy et al, 2013). In an Ugandan study, the visual analog scale (VAS) score was significantly improved in patients receiving TB treatment over a period of 6 months.…”
Section: Observationsmentioning
confidence: 99%